Effect of Acute Moderate Intensity Aerobic Exercise on Attributes 0f Sleep Among Insomniac University Students: A Pilot Study (International Journal of Physiotherapy, 2025)
Background: A student life is full of challenges and opportunities. Academic stress, the use of modern-day gadgets such as smartphones and tablets, the modern lifestyle, and many other contributing factors can lead to difficulty in sleeping. Poor sleep has been associated with a lack of focus, concentration, psychological and psychosomatic issues. The impact of exercise on various sleep disorders and sleep attributes among a university student population is relatively limited. This study aims to investigate the effect of acute moderate-intensity aerobic exercise (AMIAE) on insomnia and daytime sleepiness among insomniac university students.Methods: 31 (67% females, 32.3% males) healthy sedentary undergraduate university students suffering from insomnia symptoms (Athens’ insomnia score) have participated in the study. A single bout of moderate intensity aerobic exercise with a duration of 30 minutes, excluding warm up and cool down, given at the intensity (determined by 40% to